Shattered Lives: Persistence Violence, State Failure and Frospects of Peace in DRC - Mohamud Sheikh, Shamsi (My University, 2013)
DRC conflict is a very complex conflict with so many factors coming into play: colonial rule, legacy of exploitation, wars involving nine neighbouring countries and multiple rebels operating in the country undermining the government are just but a few problems the country is facing.Further complication of the conflict arises from the fact that natural resources became tied to the events occurring in the country, culminating into a series of rebel movements,rebellions,regional war and wars over resources all occurring in one country.DRC's stabilisation can be achieved by military reforms,police reforms,judicial reforms,African Union intervention and decentralization of power.This thesis highlights major factors sustaining violence in the eastern provinces of DRC.Findings indicate that although regional involvement and natural resources abundance provide basis for waging terror and siege control over mineral rich areas; internal weakness within DRC rooted in its history is the foundation of everything wrong with the country.The thesis examines how persistent violence in the eastern province is linked to coltan extraction and land governance,it assesses regional hold on DRC and how it is tied to instability and also looks at prospects of peace.This research relied on qualitative method.
Keywords: Business; Congo (Democratic Republic) -- History -- 1997-; Congo (Democratic Republic) -- Social conditions; Congo (Democratic Republic) -- Ethnic conflict; Peace-building -- Africa, East